How should I treat a complex left subclavian artery stenosis involving the vertebral artery in a patient with subclavian steal syndrome and left internal mammary artery bypass graft? - Ibrahim, Tareq; Langwieser, Nicolas; Dommasch, Michael; Wildgruber, Moritz; Laugwitz, Karl-Ludwig (EuroIntervention, 2015)
BACKGROUND: A 68-year-old male smoker presented with progressive symptoms of vertebrobasilar insufficiency and angina. His past medical history included arterial hypertension, diabetes mellitus, dyslipidaemia as well as diffuse coronary artery disease including left main disease. Of note, he had undergone coronary bypass surgery 12 years earlier utilising the left internal mammary artery. INVESTIGATION: Physical examination, laboratory tests, duplex ultrasound imaging, contrast-enhanced magnetic resonance imaging and coronary angiography. DIAGNOSIS: Severe bifurcation stenosis of the left subclavian and vertebral artery with consecutive subclavian steal syndrome and myocardial ischaemia. MANAGEMENT: Bifurcation T-stenting using a self-expandable bare metal and a coronary drug-eluting stent.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Bare metal stent; Drug-eluting stent; Peripheral intervention; Subclavian artery; Subclavian steal syndrome; T-stenting technique; Vertebral artery